The Effect of Moringa Oleifera Leaves Powder to Level of Serum Superoxide Dismutase (Sod), Lead (Pb), Zink (Zn)And Memory Function of Rat (Rattus Norvegicus) Wistar Strain Model of Autism That is Exposed by Pb - Agustiana Dwi Indiah Ventiyaningsih; Hidayat Sujuti; Winda Nurtika; Septi Nur Rachmawati; Nurshalilah Nurshalilah; Raudhatul Jannah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Lead exposure (Pb) may aggravate the decrease in serum SOD levels, memory function reduction and social interaction in autism. This study aims to determine the effect of Moringa oleifera on autism models of rat exposed to lead. The five groups of rat exposed to tin were studied: normal rat (C -), autistic rat (C +) and autism rats given 180 mg (T1), 360 mg (T2) or 720 mg (T3) oleifera leaves powder. Lead acetate is given through a filler tube (0.5 gr / kg) and powdered moringa leaves mixed with feed. The results showed that serum SOD levels were lower in autistic rat than normal rat and intake of Moringa olifeifera leaves powder increased serum SOD levels in autistic rats but was not seen in normal rat. The autistic rat had higher lead levels but lower zinc levels, which were not influenced by Moringa olifeira. The social interaction between rats is strongly influenced by unbidden lead with Moringa olifeira, both in normal rat and in autistic rat. Moringa oleifera will increase serum SOD levels in autistic rats but not at normal levels. Moringa olifeira does not protect significantly rat from lead causing less social interaction, nor does it lower serum Pb levels or increase Zn levels. Moringa leaves powder does not affect memory significantly.